Effect of process parameters and biomass composition on flat-die pellet production from underexploited forest and agricultural biomass. (15th October 2021) - Lavergne, Simon; Larsson, Sylvia.H.; Da Silva Perez, Denilson; Marchand, Muriel; Campargue, Matthieu; Dupont, Capucine
Highlights: 10 biomasses were pelletized in a flat-die pelletizer under minimum 6 conditions. Operating conditions had to be adjusted depending on the feedstock. Pelletizing moisture content showed correlations with extractives content. Energy input showed correlations with the acetyl groups content of the feedstock. Abstract: This study investigates the impact of biomass moisture content, press-channel length, energy input, and die temperature on pellet quality in pilot-scale flat-die pellet production. In addition, observed correlations between pellet quality and the chemical composition of the pelletized biomass assortments are presented. Ten different feedstock assortments: Scots pine bark, Scots pine forest residues, willow, poplar stemwood with bark, beech stemwood with bark, wheat straw, reed canary grass, corn cobs, sunflower shells, and grape seed cakes were pelletized in a flat-die pilot-scale pelletizer with a die-channel diameter of 6 mm. The die-channel length varied within a range of 18–60 mm and biomass moisture content from 10% to 23%. In all, 72 pelletizing experiments were performed. Biomass moisture content was the most important parameter for mechanical durability. The feedstock moisture content required to obtain maximum pellet durability depended on the feedstock and showed correlations with its extractives and galactose content. For all feedstocks, bulk density correlated negatively with moisture content. The mechanical durability and bulk density of pellets increased with energy consumption. Energy consumption increased with press-channel length and was correlated with acetyl-group content.